2021
DOI: 10.3390/ijerph18189631
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Sustainability Effects of High-Intensity Interval Exercise and Moderate-Intensity Continuous Exercise on Cognitive Flexibility

Abstract: This study examined the immediate and sustained effects of high-intensity interval exercise (HIIE) and moderate-intensity continuous exercise (MICE) on cognitive flexibility in young adults. Participants (n = 56) engaged in (1) a session of HIIE, involving 10 sets of one-minute treadmill running at an intensity targeting 90% heart rate reserve (HRR) interspersed with self-paced walking at 50% HRR; (2) a session of MICE, involving a 20 min treadmill running at an intensity of 40–59% HRR; and (3) a control sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Previous studies have demonstrated that HIIE was a more effective strategy for improving inhibitory control and cognitive flexibility compared to MICE ( Tian et al, 2021a , b ). In the present study, we provide evidence that HIIE is also effective in improving working memory.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that HIIE was a more effective strategy for improving inhibitory control and cognitive flexibility compared to MICE ( Tian et al, 2021a , b ). In the present study, we provide evidence that HIIE is also effective in improving working memory.…”
Section: Discussionmentioning
confidence: 99%
“…The workload may be sustained with moderate intensity overall to the subject. The physiological consequences of the workload is to supply of sufficient oxygen to the brain physical arousal (Tian et al, 2021) [15] . Exercise intensities especially moderate intensity is highly corelated with brain activation and executive function of the brain (Mehren et al, 2019) [11] .…”
Section: Discussion On Findingsmentioning
confidence: 99%
“…This effect has also been extended to obese populations ( Chang et al., 2017 ; Logan et al., 2021 ; Napoli et al., 2014 ; Peven et al., 2020 ; Secor, 2020 ). However, a growing body of literature suggests that high-intensity interval exercise (HIIE) is as effective or perhaps more effective than traditional moderate-intensity aerobic exercise in facilitating cognitive function and inhibitory control among healthy-weight adults ( Ai et al., 2021 ; Kao et al., 2018 ; Kao et al., 2017 ; Tian et al., 2021 ). HIIE was initially shown to improve cardiorespiratory fitness and body composition ( Alves et al., 2017 ; Delgado-Floody et al., 2019 ; Huang et al., 2022 ; Wewege et al., 2017 ) but more recent research has also extended the benefits of HIIE to cognitive function ( Ai et al., 2021 ; Alves et al., 2014 ; Hsieh et al., 2021 ; Kao et al., 2018 ; Kao et al., 2017 ; Roig-Hierro et al., 2023 ; Tian et al., 2021 ; Tsai et al., 2021 ; Tsukamoto et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%